PENGARUH PENGGUNAAN KAFEIN TERHADAP VO2Max DAN DENYUT NADI SETELAH LATIHAN PADA ATLET JUNIOR KARO TAEKWONDO CLUB - Julius Boy Nesra Basgimata Barus; Janwar Frihasan Sinuraya; Tommy Hejeprinta (JURNAL CURERE, 2022)
Coffee is a psychostimulant drink used by athletes as a supplement when they are training, because the coffee content affects physical activity with the content of the CNS in it. In addition, the methylxanthine group contained in caffeine has an effect on increasing heart rate and frequency. So that the positive benefits arising from the use of coffee became the basis for conducting this research. The purpose of this study was to determine the effect of caffeine use on VO2max and pulse rate after exercise in Junior Karo Taekwondo Club athletes. This research is an experiment with a research design "pre-post control group design". The sample in this study used the slovin formula, so that a total sample of 60 participants was obtained. This treatment was given 12 meetings and in a week there were 3 meetings. This pulse measurement will use an oximeter. The results of this study, the average value of VO2max based on the fatigue time of the control group was 30.5612 ml/kg/minute, the treatment group was 33.8532 ml/kg/minute. Meanwhile, VO2max based on the control group's pulse was 135.501 times/minute ml/kg/minute, the treatment group was 140.145 ml/kg/minute (T-paired test data analysis with 95% significance). The average post-test pulse rate for the control group was 135,401 times/minute, the treatment group was 140,145 times/minute. The pulse recovery time was obtained when the average pretest pulse rate was 85.8 beats/minute, the control group reached the initial value at the 14th minute, while the treatment group reached the initial value at the 10th minute after exercise.